International environmental risk management : a systems approach - Woellner, Robert A.; Voorhees, John; Bell, Christopher L. (Boca Raton, FL : CRC Press, 2020)
"Based on the first edition with extensive analysis of practical applications of ISO 14000 and environmental compliance management systems, the second edition reflects ISO 14001 and makes available a frame of reference and systematic approach to effectively manage environmental risk. It provides a pathway for readers to understand and systematically implement environmental management systems that symbiotically support: enterprise risk management programs; compliance, anti-bribery, and legal management systems; and product stewardship, carbon footprint assessments, and sustainability programs. Provides indepth discussion of ways to use global environmental management standards"--
OCLC-licensed vendor bibliographic record.
Keywords: Environmental risk assessment -- United States; Environmental management -- Standards -- United States; ISO 14000 Series Standards; LAW / Environmental; NATURE / Environmental Conservation & Protection; TECHNOLOGY / Environmental Engineering & Technology